SATIRE ANALYSIS IN FOUR LIONS FILM THROUGH SAUSSUREAN SEMIOTICS - Nia Denisa; Dadan Rusmana; R. Myrna Nur Sakinah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study intends to reveal the satire about Jihad concept misunderstanding which causes negative image for Islam that caused by irresponsible British Moslems. They act without sufficient religious understanding and only out of lust to get rid of the unjust infidels towards minority Moslems. So, with the analysis of the signifier-signified of Saussure's semiotic theory, it’s hoped that satire can be conveyed, understood and aware by the parties who become the targets of satire. This study has a significance for eliminating misunderstandings about Islam which are always associated with terrorism, namely stupid acts that only harm fellow Moslems. This study will use a qualitative method because it related to phenomena in society. In this study, film as the object where the data are collected and supported by literature studies. The results from 20 data contain signifier and signified of radical Moslem’s act who misunderstanding about Jihad then satire that is intended to prove those who deviate are not acting in the name of Islam, terrorism is a stupid act and British government must be more fair to minorities. It’s recommended for further studies to examine Islamophobia in Asia with poster as the object the uses qualitative method and Peircean semiotics.